Optimization of Services Through the Development of a Website-Based Online Queueing System - Iqbal, Arifal Muhamad; Sari, Dian Permata (INOVTEK Polbeng - Seri Informatika, 2025)
This study developed a web-based online queue system using the SDLC Prototype model to improve administrative service efficiency at PT. XYZ. System performance was evaluated by comparing the manual process with the new system using M/M/1 queueing theory parameters, including waiting time, service time, no-show rate, and service capacity. Observations indicated significant improvements: service time decreased from 8 minutes to 6 minutes, waiting time reduced from 28–32 minutes to 5–9 minutes, queue length decreased, and service capacity increased from approximately 35 to 45 participants per day. The no-show rate also dropped from 23–28% to 4–7% after participants could monitor the queue in real time. Usability testing was conducted using the System Usability Scale (SUS) with 23 respondents (15 participants and 8 staff). Scores were calculated using the standard odd-even item transformation, yielding an average of 84.89, categorized as “Good.” Participants generally gave higher scores than staff due to the complexity of the admin dashboard. These findings indicate that the system not only functions properly but also provides a measurable impact on improving service efficiency.